Uv Extreme Events in Northeast of Brazil - Lopo, Alexandre Boleira; Spyrides, Maria Helena Constantino; Lucio, Paulo Sérgio; Silva, Sebastião Milton Pinheiro da (Ciência e Natura, 2014)
The main objective of this paper is to analyze extremes UV episodes in Northeast of Brazil (NEB), generally associated to cloud cover and levels of total ozone column (total ozone). The methodology consisted of the calculation of the 95th percentile to define the extreme value in the seasons of UV in city of Natal-RN (reference city) and analysis of NEB obtained from Ozone Monitoring Instrument (OMI) to UV index, total ozone and cloud cover in dates of extreme events in reference city. The results of UV index for Natal city indicated 14.4 for the extreme event in summer and images selected of OMI showed that extreme event were associated mainly with absence of cloudiness and levels below average annual of total ozone. Analysis of extreme episodes of UV index in NEB indicated that the extreme event occurred in reference city does not happen in the entire region, because of the large spatial variability of cloud cover and total ozone.